2012
DOI: 10.1080/15295192.2012.638871
|View full text |Cite
|
Sign up to set email alerts
|

African American and European American Mothers' Beliefs About Negative Emotions and Emotion Socialization Practices

Abstract: SYNOPSIS Objective Mothers’ beliefs about their children’s negative emotions and their emotion socialization practices were examined. Design Sixty-five African American and 137 European American mothers of 5-year-old children reported their beliefs and typical responses to children’s negative emotions, and mothers’ emotion teaching practices were observed. Results African American mothers reported that the display of negative emotions was less acceptable than European American mothers, and African America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 53 publications
(76 reference statements)
9
122
1
2
Order By: Relevance
“…Prior work has shown that depressed mothers of boys tend to show more negative affect and intrusiveness in their interactions with their sons compared to depressed mothers of daughters [36,62]. Other research suggests that African American mothers generally interact with sons and daughters in similar ways during the early years of life [63], but may respond in less supportive ways when their sons display negative emotions compared to their daughters [64]. Mothers who are depressed prenatally may be less sensitive and responsive in the days and months following the birth, leading their infants to respond with elevated levels of negative emotion.…”
Section: Discussionmentioning
confidence: 93%
“…Prior work has shown that depressed mothers of boys tend to show more negative affect and intrusiveness in their interactions with their sons compared to depressed mothers of daughters [36,62]. Other research suggests that African American mothers generally interact with sons and daughters in similar ways during the early years of life [63], but may respond in less supportive ways when their sons display negative emotions compared to their daughters [64]. Mothers who are depressed prenatally may be less sensitive and responsive in the days and months following the birth, leading their infants to respond with elevated levels of negative emotion.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, low mother-child openness, indexed by mothers’ reports of low levels of child emotion sharing and comfort seeking from the mother as well as low levels of trust in and reliance on the mother, was associated with depressive symptoms for European American children but not African American children (Vendlinski et al, 2006). Finally, African American children whose mothers encouraged them not to express their negative emotions were rated higher on social-emotional competence by their teachers; this association was not apparent for European American children (Nelson et al, 2012). The latter result suggests that some forms of non-supportive emotion socialization may be adaptive for African American children.…”
Section: Introductionmentioning
confidence: 86%
“…However, in four recent studies in which ethnicity was examined as a moderator of the effect of non-supportive practices on social-emotional outcomes a different pattern was apparent among African American families (Leerkes et al, 2012; Montague et al, 2003; Nelson et al, 2012; Vendlinski et al, 2006). Specifically, the association between remembered punitive emotion socialization in childhood and fearful/preoccupied adult attachment was significantly stronger for European American adults than African American adults (Montague et al, 2003), and remembered parental emotion minimization in childhood was linked with elevated depressive symptoms for European American women but not African American women (Leerkes et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bu annelerin çocuklarının akademik başarıları ve problem çözme becerileri yüksek, sosyal kaygıları da düşüktür. Duygusal sosyalleştirmeye anne-babaların eğitim düzeyinin etkisinin yanında kültürün etkisi ile ilgili yapılan bir çalışmada (Nelson, Leerkes, O'Brien, Calkins ve Marcovitch, 2012) annelerin 5 yaş çocuklarının olumsuz duygularını sosyalleştirmesi incelenmiştir. Araştırmaya 65 Afrika ve Avrupa kökenli anne katılmıştır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified